2019
DOI: 10.21608/ejabf.2019.35100
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of larvicidal activity of nanoemulsion from Citrus sinensis essential oil on Culex pipiens L. (Diptera: Culicidae)

Abstract: Larvicide UltrasonicationSynthetic insecticides cause pollution to the environment. In addition, insects develop resistance toward them. So, there is an urgent need for effective safe alternatives. In the current study, nanoemulsion was prepared from essential oil of Cirtus sinensis by the ultrasonic method. The efficacy of the nanoemulsion was evaluated against larvae of Culex pipiens and compared with that of the bulk emulsion. The mean droplet size of the nanoemulsion was 78.8±14.2 nm with poly dispersity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The larvicidal activity of the nanoemulsion of P. anisum against the C. pipiens larvae in this study may be due to trans-anethole which is the major component of the EO, it was reported to have insecticidal property ( Abdel-Baki et al, 2021) . Our results agree with several studies on the nanoemulsions based on EOs as effective insecticides (Anjali et al, 2011;Ghosh et al, 2013;Sugumar et al, 2014;Duarte et al, 2015, Azmy et al, 2019Azmy et al, 2021a). In addition, the results of this research come in contact with the research that studied the toxic effects of P. anisum EO on the different life stages of Cx.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The larvicidal activity of the nanoemulsion of P. anisum against the C. pipiens larvae in this study may be due to trans-anethole which is the major component of the EO, it was reported to have insecticidal property ( Abdel-Baki et al, 2021) . Our results agree with several studies on the nanoemulsions based on EOs as effective insecticides (Anjali et al, 2011;Ghosh et al, 2013;Sugumar et al, 2014;Duarte et al, 2015, Azmy et al, 2019Azmy et al, 2021a). In addition, the results of this research come in contact with the research that studied the toxic effects of P. anisum EO on the different life stages of Cx.…”
Section: Discussionsupporting
confidence: 91%
“…EO Nanoemulsions are emulsions with droplet size in the nano-range (McClements, 2011); this formulation improves solubility of oils (Magdassi et al, 2013). Many EOs nanoemulsions were reported as effective larvicides such as nanemulasions of eucalyptus, rosemary, orange (Sugumar et al, 2014;Duarte et al, 2015, Azmy et al, 2019Azmy et al, 2021 a). P. anisum belongs to family Apiaceae, the EO of this plant can be extracted from the seeds, the major component of P. anisum EO is trans-anethole (Orav et al, 2008), the insecticidal activity of this compound was reported against C. pipiens (Zoubiri et al, 2014;El Zayyat et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…EOs are also known for use in controlling insects due to their volatility properties, which makes them suitable for fumigation [42]. Some authors demonstrated the increase of jojoba oil concentration causes the rise of death in rice weevil, Sitophilus oryzae adults [43]; the mortality rate of mosquito larvae also increases when surfactants are used higher in neem oil nanoemulsions and Citrus sinensis nanoemulsions, respectively [44,45]. Therefore, it was concluded that the mortality rate of pest is dependent on both surfactant and oil concentration in the nanoemulsions.…”
Section: Surfactant As An Emulsifier In Nanoemulsionmentioning
confidence: 99%
“…pipiens to possess certain water solubility as it is an aquatic insect which was difficult to achieve with the EOs. 9 The lipoid nature of the EO could hinder the penetration of oil through the mosquito and thus it was critical to encapsulate the EO in a suitable formulation to enhance its insecticidal effect. Hexosomal nano-particles were the most convenient as GMO, which is one of its lipid components that is able to incorporate both hydrophilic and lipophilic constituents.…”
Section: Metabolic Proling Of Valencia Orange Leaves Essential Oils ...mentioning
confidence: 99%
“…pipiens mosquitos. 6,9 Various techniques are utilized for the extraction of essential oil from the plant such as solvent extraction, steam-hydrodistillation, steam distillation, and hydrodistillation. 10,11 Hydrodistillation is the most common technique for essential oil extraction on small or industrial scale.…”
Section: Introductionmentioning
confidence: 99%